2019
DOI: 10.1016/j.fertnstert.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Uterine polyps, adenomyosis, leiomyomas, and endometrial receptivity

Abstract: Endometrial polyps, adenomyosis, and leiomyomas are commonly encountered abnormalities frequently found in both fertile women and those with infertility. The clinician is frequently challenged to determine which of these entities, when found, is likely to impair fertility, and which are ''innocent bystanders'' unrelated to the problem at hand. Although removing an endometrial polyp may be seen as a relatively benign and safe intervention, myomectomy, and in particular adenomyomectomy, can be substantive surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 139 publications
2
120
0
8
Order By: Relevance
“…It is important to point out that in the stromal component of endometrial polyps there is a lower number of hormone receptors. Therefore, the glands and stroma of polyps do not respond to progesterone stimulation, which may be the cause of abnormal secretion of progesterone in the endometrium [27,28,29]. A study that measured TNF-α concentration in uterine flushings of 12 patients before and after hysteroscopic polypectomy showed an increase in TNF-α concentrations after polyp removal with TNF-α values reaching the peak in the midluteal menstrual cycle phase [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that in the stromal component of endometrial polyps there is a lower number of hormone receptors. Therefore, the glands and stroma of polyps do not respond to progesterone stimulation, which may be the cause of abnormal secretion of progesterone in the endometrium [27,28,29]. A study that measured TNF-α concentration in uterine flushings of 12 patients before and after hysteroscopic polypectomy showed an increase in TNF-α concentrations after polyp removal with TNF-α values reaching the peak in the midluteal menstrual cycle phase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although adenomyosis has been considered a typical uterine condition identified in multiparous women over the age of 40, recent studies and modern diagnostic imaging methods have demonstrated the presence of this disease in young women as well. Regarding the association with infertility and reproductive failure the evidence suggests that the percentage of adenomyosis prevalence is variable between 20% and 40% in cases of recurrent pregnancy loss, and about 35% was reported in previous ART failure [ 101 , 102 , 103 , 104 , 105 ].…”
Section: Mechanisms Involved In the Pathogenesis Of Endometriosis-mentioning
confidence: 99%
“…For endometrial preparation, the orchestrated control of estradiol (E2) and progesterone (P4) produced by the ovaries induces proliferative changes and development of a secretory phase, both required for 2 of 21 embryo-endometrial synchronicity [1]. Upon P4 stimulation, the process of decidualization begins with a complex and coordinated set of molecular events that result in endometrial receptivity [2]. During decidualization, P4 influences the secretion of bone morphogenetic protein (BMP)-2 by the endometrial stromal cells to proliferate and differentiate into epithelioid decidual cells that are critical to the establishment of fetal-maternal interface [3].…”
Section: Well-functioning Endometrium Is Essential To Ensure Embryo Imentioning
confidence: 99%
“…Regulation of uterine peristalsis (UP) is also a relevant factor for conception and embryo implantation since UP disorders are associated with low fertility rate and may contribute to the pathogenesis of adenomyosis and endometriosis in addition to failure in sperm and embryo transport [2,12]; these UP-associated pathologies are observed in normal and infertile women and influence pregnancy in both natural and artificial cycles.…”
Section: Well-functioning Endometrium Is Essential To Ensure Embryo Imentioning
confidence: 99%